Pemberdayaan Anak Jalanan di Rumah Musik Yayasan Kelompok Kerja Sosial Perkotaan Medan - Sinulingga, Ferdinan; Hodriani, Hodriani (Universitas Medan Area, 2015)
The purpose of this study was to determine program effectiveness empower street children and street children empowerment program that has been done in the House of Music on Foundations of Urban Social Working Group (KKSP). The study population was the whole street children in the House of Music - KKSP who move the red light intersection Simpang Pos totaling 193 street children. Samples were taken 10% of the number of street children that 20 street children. The method used is descriptive qualitative. Instrument filtering the data used were interviews and observation and tabulation of the data contained in a single tabulation. From this research, the writer can say that the empowerment of street children has been done in the House of Music - KKSP have some kind of empowerment programs such as the field of non-formal education, the arts of music and sports. Program services in the field of non-formal education and the art of music in its implementation has been effective because it has been the achievement of each of these programs. While services in the field of exercise undertaken by the manager of street children is still not effective. Limitations fasilisas and supplies to make street children prefer to practice the skills of music rather than sports.